Management of a difficult infectional disease: Descending necrotizing mediastinitis - Fazlı Yanık; Yekta Altemur Karamustafaoğlu; Yener Yoruk (Journal of Infection in Developing Countries)
Introduction: Descending Necrotizing Mediastinitis (DNM) is the fatal form of mediastinitis and mostly develops as a complication of peritonsillar abscesses or dental-odontogenic infections. The aim of this study is to evaluate clinical and surgical feature of the patients with DNM who were managed in our clinic.